Parental Communication Patterns In Reducing Children's Dependence On Playing Gadgets - Sihombing, Lourensia; Veranus Sidharta; Wenny Maya Arlena (LPPM Stikosa - AWS, 2024)
Easy access to digital content such as online games, social media, and video streaming, makes gadgets an integral part of children's daily lives that are excessive. Children become dependent on gadgets so that they can have a negative impact on their social, emotional, and physical development. In dealing with these negative impacts, parents are faced with the need to adopt communication patterns that can direct and guide children in using gadgets more wisely. This study explores how effective communication patterns can create an environment that supports reducing gadget dependence. This study uses a qualitative descriptive method. The unit of analysis in this study is parental communication patterns, especially how parents interact and communicate with children regarding gadget use. The subjects of the study were two housewives with the initials Mama-Al and Mama-An who live in Taman Wisma Asri Housing RT 002, North Bekasi. The results of the study showed that Mama-Al and Mama-Anjani combined an authoritative, open, and emotional approach in reducing children's dependence on gadgets. Protective communication patterns help in maintaining gadget usage limits, pluralistic communication patterns facilitate healthier dialogue and social interaction, while sensual communication patterns emphasize discipline with sensitivity to children's emotional needs. The combination of these three patterns creates a balanced environment and supports children to reduce their dependence on gadgets in an effective and sustainable way.